Wilms' tumor gene 1 immunotherapy in pelvic gynecological malignancies. (June 2014) - Coosemans, A; Vergote, I; Van Gool, SW
<x xml:space="preserve">Abstract</x> Pelvic gynecological malignancies account for 6% of all cancers. In the relapsed state, classical treatments are limited. There is an urgent need for new and personalized treatment. Wilms' tumor gene 1 (WT1) is the most important tumor-associated antigen. Although highly present in gynecological tumors, active immunotherapy against it is still underexplored. This review gives an insight into the importance of WT1 in pelvic gynecological malignancies and the first taken steps into the world of WT1 immunotherapy.